Laser–particle interaction-based analysis of powder particle effects on temperatures and distortions in directed energy deposition additive manufacturing. Issue 9 (2nd September 2021) - Zhang, Z.; Ge, P.; Li, J. Y.; Wang, Y. F.; Gao, X.; Yao, X. X.
Abstract: In order to investigate the interactions between laser and powder particles in directional energy deposition (DED) additive manufacturing (AM), a coupled electromagnetic wave heating (EWH) model is proposed. The heat transfer reduction coefficient for the laser beam power can be calculated, and then the temperature distributions can be obtained based on the modified heat source model. A comparison of the predicted temperature and that obtained in the experiment using infrared radiation thermometer validates the proposed models. The residual distortion of the additive manufactured specimen was measured in experiment and then studied in detail using the numerical model. The powder quality can affect the number of particles in the laser's electromagnetic wave, as well as the laser power that a layer of particles absorbs. As a result, it can affect the heat transfer reduction coefficient in DED, along with the thermal histories and temperature distributions. Thus, the final residual distortion can be changed and controlled by the powder. In addition to the powder particle parameters, the thickness of the substrate and location of the deposition layers on the substrate can also significantly influence the residual distortion of the deposition product in DED.